Biography of A.M. Sangadji in History Learning: Strengthening Nationalism and Student Leadership - Kubangun, Nur Aida; Far-Far, Gazali; Pattiasina, Johan (Ilomata International Journal of Social Science, 2025)
This research uses the Library Research method because the data is obtained through various sources in the form of books, excyclopedias, journals, documents, etc. In general, the data contained in research results are obtained from articles published online in various national journals, and research reports from the Maluku TP2GD Team, as well as articles published in online media that are relevant to the research. The steps taken include collecting library data, reading, taking notes, and comparing literature and then processing it and producing conclusions. Meanwhile, the data analysis used is content analysis. The data collected is descriptive textual data, so processing the data uses analysis according to its content, which is called content analysis. The research results explain that A.M.'s struggle. Sangadji was hit by a spirit of nationalism due to policies implemented by the Dutch East Indies government which tended to be unfair to the native people. Apart from that, the meaning of leadership for an A.M. Sangadji is more about the role and function of a leader. This means that the leader understands only his structural position, but more about his role in fighting for the interests of the wider community without looking at a particular region or region. So the biography of A.M. Sangadji, when applied as a learning resource in history learning, can strengthen students' spirit of nationalism and leadership.